Asset Diversification versus Climate Action - Christoph Hambel; Holger Kraft; Rick van der Ploeg (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Asset pricing and climate policy are analyzed in a global economy where consumption goods are produced by both a green and a carbon-intensive sector. We allow for endogenous growth and three types of damages from global warming. It is shown that, initially, the desire to diversify assets complements the attempt to mitigate economic damages from climate change. In the longer run, however, a trade-off between diversification and climate action emerges. We derive the optimal carbon price, the equilibrium risk-free rate, and risk premia. Climate disasters, which are more likely to occur sooner as temperature rises, significantly increase risk premia.
Keywords: D81; G01; G12; Q50; Q54; 330; decarbonisation; diversification; carbon price; asset prices; green assets; disaster risk